1.5 µW wake‐up‐receiver for biotelemetry applications. Issue 11 (November 2017) - Whitehall, Sean E.; Saavedra, Carlos E.
Abstract: This article presents a microwave wake‐up receiver for biotelemetry applications. The circuit is designed using 130 nm CMOS technology and it consists of a passive amplification front end filter, envelope detector and baseband frequency amplifier with variable feedback filtering. The receiver is designed to operate at 7.6 GHz and measured results show that it has a sensitivity of −40 dBm while drawing just 3 μA from a 0.5 V supply. The presented work has the smallest known area and exhibits a competitive tradeoff between DC power, sensitivity, and bit rate.